A ancestralidade e o mulherismo africana em Diário de Bitita, de Carolina Maria de Jesus - Fleischmann, Fransueiny Pereira (2022)
The present dissertation presents as its central theme the critical-literary analysis of the work Diário de Bitita (1982) by the writer Carolina Maria de Jesus from African traditions such as ancestry and African women. To this end, the fabric takes place around theorists who move away from the Eurocentric conception, and who, on the contrary, place African traditions at the heart of the epistemological issues of black Brazilian literature. In relation to ancestry, this will be referenced to African heritages seen in the work, such as ancestral memory, oral tradition and the author's bond with Mother Earth. The research will follow around the representation of women from the African women's perspective and from a decolonial gender perspective. As a theoretical contribution, researchers who have focused on the research theme will be used, such as Eduardo Oliveira (2021), Leda Maria Martins (2001), Fábio Leite (1997; 2008), Michele Freire Schiffler (2014), Nei Lopes and Luiz Antônio Simas (2020), Amadou Hampaté Bâ (2010), Clenora Hudson Weens (2018), Nah Dove (1998) and Françoise Vergès (2020).